A case of intravascular large B cell lymphoma: New clinical and immunohistochemical findings. Issue 5 (18th April 2016) - Mansueto, Gelsomina; Di Vito, Anna; Belluomo, Clara; Murino, Patrizia; Natella, Valentina; Camastra, Caterina; Presta, Ivan; Malara, Natalia; de Rosa, Gaetano; Donato, Giuseppe; Mignogna, Chiara
Abstract : Intravascular large B cell lymphoma (IVLBCL) is a rare extranodal non‐Hodgkin lymphoma characterized by proliferation of malignant cells within the lumen of small vessels, with a predilection for the CNS and the skin. IVLBCL clinical course is highly aggressive, clinical signs and symptoms are not specific and may consist of neurological and cognitive impairment, fever of unknown origin and cutaneous lesions, lacking of a typical neuroimaging pattern. For all these reasons the diagnosis is commonly missed and the exitus is frequent, therefore post mortem evaluation is necessary to clarify the clinical history. We present a case of IVLBCL in a 62‐year‐old woman with unusual symptomatology, mimicking a vascular, multi‐infarctual cerebropathy. Hachinski Ischemic Score was 7 suggesting a vascular dementia. Autopsy was unable to define the nature of the disease. Immunohistochemical analysis for cluster of differentiation 20 (CD20) revealed the ubiquitous presence of malignant lymphoid B‐cells into the vessel of all organs analyzed, allowing the definitive diagnosis of IVLBCL. The atypical cells expressed high levels of anti‐apoptotic proteins B‐cell lymphoma 2 (Bcl‐2) and Galectin‐3, and showed cellular myelocytomatosis (c‐Myc) staining in <50% of tumor nuclei. Conversely, cells were immunonegative for multiple myeloma‐1 (MUM1), CD3, CD44, CD30, CD34 and CD133. Fluorescent in situ hybridization analysis for MYC rearrangements was negative. The high expression of Galectin‐3 provides new insights in the understanding of molecular pathogenesis of IVLBCL; indeed, such a finding represents a prognostic factor for other types of lymphoma and should, in the same way, be taken into account in IVLBCL.